2021
DOI: 10.1103/physrevlett.126.095101
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Field Amplification by the Weibel Instability at Planetary and Astrophysical Shocks with High Mach Number

Abstract: Collisionless shocks are ubiquitous in the Universe and often associated with a strong magnetic field.Here, we use large-scale particle-in-cell simulations of nonrelativistic perpendicular shocks in the high-Mach-number regime to study the amplification of the magnetic field within shocks. The magnetic field is amplified at the shock transition due to the ion-ion two-stream Weibel instability. The normalized magnetic field strength strongly correlates with the Alfvénic Mach number. Mock spacecraft measurements… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 43 publications
6
21
0
Order By: Relevance
“…Perhaps, a larger growth rate driven by the unmagnetized non-gyrotropic beam will push the system into the filament merging phase before the ions behave magnetized Ω i t 1. The nonlinear evolution then becomes essentially the same as the unmagnetized plasma case, in which the magnetic field may be amplified to reach essentially the Alfvén current limit 26,27,30 . On the other hand, the saturation in most of our simulations presented in this paper occurs typically at Ω i t ∼ 1, beyond which the ions start to behave magnetized.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Perhaps, a larger growth rate driven by the unmagnetized non-gyrotropic beam will push the system into the filament merging phase before the ions behave magnetized Ω i t 1. The nonlinear evolution then becomes essentially the same as the unmagnetized plasma case, in which the magnetic field may be amplified to reach essentially the Alfvén current limit 26,27,30 . On the other hand, the saturation in most of our simulations presented in this paper occurs typically at Ω i t ∼ 1, beyond which the ions start to behave magnetized.…”
Section: Discussionmentioning
confidence: 96%
“…Oscillatory features observed in the terrestrial bow shock are sometimes attributed to the rippling mode 24,25 . More recent PIC simulations for high Mach number non-relativistic perpendicular shocks, relevant to young supernova remnant (SNR) shock, suggested that the electromagnetic fluctuations at the ion scale driven by the reflected ions are instead generated by the Weibel instability [26][27][28][29][30] . In contrast to the rippling mode, in which fluctuating magnetic field amplitudes are of the same order of the background field, the Weibel instability amplifies the magnetic field to a level much larger than the background field.…”
Section: Introductionmentioning
confidence: 99%
“…Particle positions are updated using the Vay solver (Vay 2008). When applied to perpendicular shocks, the data from these simulations have proven to accurately reproduce the fundamental physical processes present in larger and computationally more expensive full 3D simulations (e.g., Bohdan et al 2017;Matsumoto et al 2017) and measured in situ (Bohdan et al 2020a(Bohdan et al , 2021. This version of the code also permits the tracing of individual particles, where we can track the components of their velocities and local fields, allowing for a detailed analysis of the underlying physical processes.…”
Section: Simulation Setupmentioning
confidence: 99%
“…The fully kinetic Particle-in-Cell (PIC) simulation has been the most powerful tool for the purpose. Starting from early simulations in one dimension (1D) (e.g., Shimada & Hoshino 2000;Hoshino & Shimada 2002;Scholer et al 2003), recent simulations have been performed routinely in two dimensions (2D) (e.g., Amano & Hoshino 2009;Umeda et al 2012a;Tran & Sironi 2020;Bohdan et al 2021) and sometimes even in three dimensions (3D) (Matsumoto et al 2017). Similarly, in-situ measurements by spacecraft, in particular at Earth's bow shock, have been used to study the electron dynamics at collisionless shocks (Feldman et al 1982(Feldman et al , 1983Thomsen et al 1987b;Scudder et al 1986;Schwartz et al 1988).…”
Section: Introductionmentioning
confidence: 99%